Association Between Circulating Proprotein Convertase Subtilisin/Kexin Type 9 and Major Adverse Cardiovascular Events, Stroke, and All-Cause Mortality: Systemic Review and Meta-Analysis - Zhou, Yimo; Chen, Weiqi; Lu, Meng; Wang, Yongjun (Frontiers in Cardiovascular Medicine, 2021)
Background: Proprotein convertase subtilisin/kexin type 9 (PCSK9), a pivotal protein in low-density lipoprotein cholesterol metabolism, has been validated to be an established target for cardiovascular (CV) risk reduction. Nevertheless, prospective studies concerning the associations between circulating PCSK9 and the risk of CV events and mortality have yielded, so far, inconsistent results. Herein, we conducted a meta-analysis to evaluate the association systemically. Methods: Pertinent studies were identified from PubMed, EMBASE and Cochrane Library database through July 2020. Longitudinal studies investigating the value of circulating PCSK9 for predicting major adverse cardiovascular events (MACEs) or stroke or all-cause mortally with risk estimates and 95% confidence intervals (CI) were included in the analyses. Dose-response meta-analysis was also applied to evaluate circulating PCSK9 and risk of MACEs in this study. Results: A total of 22 eligible cohorts comprising 28319 participants from 20 eligible articles were finally included in the study. The pooled relative risk (RR) of MACEs for one standard deviation increase in baseline PCSK9 was 1.120 (95% CI, 1.056-1.189). When categorizing subjects into tertiles, the pooled RR for the highest tertile of baseline PCSK9 was 1.252 (95% CI, 1.104-1.420) compared with the lowest category. This positive association between PCSK9 level and risk of MACEs persisted in sensitivity and most of the subgroup analyses. Twelve studies were included in dose-response meta-analysis, and a linear association between PCSK9 concentration and risk of MACEs was observed (x2 test for nonlinearity= 0.31, P nonlinearity =0.575). No significant correlation was found either on stroke or all-cause mortality. Conclusion: This meta-analysis added further evidence that high circulating PCSK9 concentration significantly associated with increased risk of MACEs, and a linear dose-response association was observed. However, available data did not suggest significant association either on stroke or all-cause mortality. Additional well-designed studies are warranted to further investigate the correlations between PCSK9 concentration and stroke and mortality.